Field appraisal of slow release formulations of acephate against mustard aphid (Lipaphis erysimi) - KUMAR, JITENDRA; NISAR, K; DEY, DEBJANI; SHAKIL, N A; A, PANKAJ; WALIA, SURESH (The Indian Journal of Agricultural Sciences, 2026)
An experiment was conducted during 2007 to study the bioefficacy of slow release formulations of acephate against mustard aphid (Lipaphis erysimi Kalt.). Slow release formulations of insecticide acephate have been prepared using commercially available polyvinyl chloride, carboxy methyl cellulose and carboxy methyl cellulose with kaolinite. These released Acephate beyond 63 days as compared to 28 days from its commercial 75 DF CMC-Kaolinite-based formulation provided a superior control (3.63%) of mustard aphid in field grown mustard (Brassica campestris L.) in comparison to acephate 75 DF (4.86%) at the dose (584 g a i/ha) after 72 days of treatment. The residue of acephate was not detected in any treatment.